High Frequency of Epstein-Barr Virus and Absence of Papillomavirus in Breast Cancer Patients from Brazilian Northeast - de Oliveira, Emanuele Silva; Ferreira, Márcia Valéria Pitombeira; Rahal, Paula [UNESP]; Branco, Martan Barroso Castelo; Rabenhorst, Silvia Helena Barem (EpiSmart Science Vector, 2022)
Objective: This study aimed to determine the presence of Epstein-Barr Virus (EBV) and Human papillomavirus (HPV) in breast cancer with patients from Northeast of Brazil, considering the molecular subtypes and also taking in account the relation with TP53 immunoexpression. Methods: Seventy-five samples of invasive breast carcinoma with no special type were selected from pathology archives at Federal University of Ceará. EBV was detected by In situ hybridization (ISH) and immunohistochemistry (IHC) and HPV was detected by PCR. ISH was performed using EBER1 probe (Shibata et al., 1991; Bacchi et al., 1996) while IHC was performed on histological formalin-fixed paraffin-embedded tissue samples (Hsu et al., 1981). PCR methodology (Haws et al., 2004) was used to amplify the genetic material of human papillomavirus. The amplification products were electrophoretic analyzed on 1% agarose gel. The data analyses were carried out using the statistical software EPINFO® version 6.04d and SPSS version 17.0 (SPSS Inc., Chicago, IL). Statistically significant differences were evaluated by the chi-square test and Fisher’s exact test and correlations between groups were analyzed by Spearman’s and Pearson’s rank correlation coefficient. Results: 69.4% of the cases were EBNA1 positives by IHC. EBNA1 positive tumors had lower Ki-67 index (0-40%), while EBNA1 negative cases had relevant higher Ki-67 index (41-100%) (p = 0.06). EBV was present in all tumor grades, with a high frequency in grade I and III tumors comparing to EBNA1 negative cases. No HPV positive cases were observed. Conclusion: Regarding the results from this study, we support the hypothesis that EBV can be involved on breast tumorigenesis
Keywords: Biomarkers; Breast; Epidemiology; Molecular oncology